The Martians - Robinson, Kim Stanley 1952- (Bantam Books, 1999)
Twenty-eight stories, including poetry, devoted to life on Mars. The story, Arthur Sternbach Brings the Curveball to Mars, is on the effect of the planet's gravity on the game of baseball, Jackie on Zo, is about childbirth on Mars, and Green Mars is on climbing a mountain.
Keywords: Science fiction, American; Mars (Planet) -- Fiction